La ‘géographie appliquée’ au service de l’expansion allemande avant 1914 - Philippe Alexandre (Recherches Germaniques)
Geographer Hugo Grothe’s case is a clear illustration of the prominent part played by a number of university disciplines, namely ‘applied geography’, in spreading the German expansionist ideology before 1914. With the help of the Emperor and the appropriate diplomatic staff some researchers launched into expeditions designed to collect data and various information likely to bring to light some areas in which German trade and power were expected to develop. A special case is Persia, a country located in an area at the very heart of the project of the Baghdad railways network, designed and carried out by the Germans. The researcher, going beyond the scope of his common skills, presented himself as an adviser and promoter of this project.Hugo Grothe was in narrow relationship with Pan-German circles and he came up with a skillfull editorial policy in order to reach a wide audience, ranging from those involved in the economy of the country to the general public that he wanted to support this idea. In his publications Persia appears as one of the most promising Western Asian countries with regard to the future development of Germany.